2003
DOI: 10.1002/hed.10260
|View full text |Cite
|
Sign up to set email alerts
|

Malignant peripheral primitive neuroectodermal tumor‐peripheral neuroepithelioma of the head and neck: A clinicopathologic study of five cases and review of the literature

Abstract: Malignant pPNET-peripheral neuroepithelioma should be included in the differential diagnosis of small, round, blue cell tumors of head and neck. A combination of multiple diagnostic modalities is essential for correct diagnosis, and multimodality treatment offers the best outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 38 publications
1
46
0
2
Order By: Relevance
“…In general, the gender distribution of patients with PNET varies among different studies. 1,3,6 We found that women slightly predominate, as distinct from the previously maxillary PNET cases reported by Shah et al in 2014 (male/female ratio of 9:10) ( Table 1). 1 As in our case, there was either as a soft tissue mass or swelling in the most of the reported cases of PNETs of the maxilla in Table 1.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In general, the gender distribution of patients with PNET varies among different studies. 1,3,6 We found that women slightly predominate, as distinct from the previously maxillary PNET cases reported by Shah et al in 2014 (male/female ratio of 9:10) ( Table 1). 1 As in our case, there was either as a soft tissue mass or swelling in the most of the reported cases of PNETs of the maxilla in Table 1.…”
Section: Discussionsupporting
confidence: 63%
“…3 The most common location of PNET in the head and neck region is the orbit; followed by the neck and the parotid gland. 4 However, peripheral PNET has also been reported in the temporal region, paranasal sinuses, skull and masseter muscle in the head and neck region.…”
mentioning
confidence: 99%
“…3,6 It is thought that the NEDT comes from the neoplastic transformation of primitive neuroepithelial cells. The fact that such cells may remain anywhere in the nervous system may explain the diverse origins of this tumor.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The peripheral NEDT on the head and neck is extremely rare, and in a recent literature review we did not see any publication of such tumor involving the temporal bone and the facial nerve canal. 3 Our goal with the present paper is to report on a patient who presented peripheral facial paralysis as initial manifestation of the peripheral NEDT involving the temporal bone. Following that, we ordered a brain and skull base MRI study; the patient returned after three weeks with a normal brain MRI and additional complaints (back pain and lower limb paresis), being admitted to the Neurosurgery department.…”
Section: Introductionmentioning
confidence: 99%
“…a Pituitary hormones and/or pituitary transcription factors, but may include or peptides and hormones (ADH, oxytocin). Based on data aggregate in part from Bahrami et al, 36 Bell et al, 51 Bishop et al, 74 Bourne et al, 143 Chapman-Fredricks et al, 88 Folpe et al, 151 Hafezi et al, 150 Hicks et al, 30 Nikitakis et al, 166 Thompson et al, 7 Thompson et al, 124 Thompson et al, 159 and Wooff et al 57 …”
Section: Melanomamentioning
confidence: 99%